2019
DOI: 10.1007/s11069-019-03762-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal assessment of drought hazard, vulnerability and risk in the Krishna River basin, India

Abstract: Spatial and temporal assessment of drought hazard over the Krishna River basin of India has been performed using long-term (January 1901-December 2002 precipitation and temperature data. Various meteorological drought indices such as the Standardized Precipitation Index, Standardized Precipitation Evapotranspiration Index, Standardized Effective Precipitation Evapotranspiration Index and Reconnaissance Drought Index (RDI) have been evaluated on a 12-month timescale for assessment of the drought hazard. Various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 48 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…Climate change has shown strongest negative impacts on the India's water resource systems, especially in last two or three decades (Jain, ). Many regions in India have been confronted with severe extreme events such as droughts and floods (Gupta and Jain, ; Sharma and Goyal, ; Singh et al ., ). Several studies utilizing global climate models (GCMs) have shown that the magnitude of precipitation extremes will be enhanced in the 21st century (Mishra et al ., ; Singh and Goyal, ; IPCC, Palazzi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Climate change has shown strongest negative impacts on the India's water resource systems, especially in last two or three decades (Jain, ). Many regions in India have been confronted with severe extreme events such as droughts and floods (Gupta and Jain, ; Sharma and Goyal, ; Singh et al ., ). Several studies utilizing global climate models (GCMs) have shown that the magnitude of precipitation extremes will be enhanced in the 21st century (Mishra et al ., ; Singh and Goyal, ; IPCC, Palazzi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It is very difficult to describe its status most of the time because of its' inherent character (Rossi 2003). The general feature of drought is peculiar, which significantly deviates from other natural hazards and disasters (Zarch et al, 2015) as it may stretch over a month or even years (Singh et al, 2019). Over 4 types of drought (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Footprints of drought are complicated and thus, require inclusion of interdisciplinary parameters for effective prediction and forecasting (Zagade and Umrikar 2021). Recently, for effective drought assessment and prediction several indices and models namely reconnaissance drought index (RDI), standardized precipitation evapotranspiration index (SPEI), groundwater drought index (GDI), enhanced vegetation index (EVI) (Thomas et al 2016;Niu et al 2019;Singh et al 2019), vegetation health index , univariate analysis coupled with climate models (Thilakarathne and Sridhar 2017) and quantitative-qualitative scoring technique (Al Qudah et al 2021) are being utilized for drought vulnerability assessment for the river basins (Udall and Overpeck 2017, Phung et al 2021, Venkatcharyulu 2021. Machine learning models have advantage over data driven model due to their good performance and wider drought prediction capabilities (Zhu et al 2021).…”
Section: Introductionmentioning
confidence: 99%